Integrating Islamic Values, Scientific Knowledge, and Digital Pedagogy in Schools: Implications for the Epistemic Transformation of Muslim Society - Firman Mansir (Ijtimā'iyya Journal of Muslim Society Research, 2026)
Research on Islam–science integration in education has often remained both normative and school-bound: it affirms the compatibility of revelation and scientific knowledge but rarely explains how classroom integration may reshape knowledge practices, authority, and public ethics in Muslim society. This article addresses that problem through a critical integrative review of 26 peer-reviewed publications issued between 2011 and July 2026. Sources were located through Crossref, ERIC, DOAJ, and Google Scholar, while foundational works on Islam, science relations, Muslim schooling, and maqāṣid al-shariah were used as supplementary analytical lenses. The synthesis identifies four modes of integration: additive-textual, interdisciplinary-curricular, ethical-teleological, and critical-transformative. Additive verse-matching is accessible but rarely alters how evidence, interpretation, or authority is evaluated. Stronger approaches link disciplinary methods, ethical purposes, teacher collaboration, community-facing inquiry, and multidimensional assessment. The review argues that schools can contribute to the epistemic transformation of Muslim society when learning strengthens scientific literacy, responsible engagement with Islamic sources, public reasoning, and the capacity to address shared problems. Islamic law is positioned as a normative framework for protecting intellect, life, dignity, and public benefit, not as a substitute for scientific validation. A five-layer framework is proposed: epistemic orientation, maqasid-based public purpose, curricular coherence, inquiry with social circulation, and digital governance with assessment. The article thereby connects school reform to Muslim-society research without claiming social effects that the current evidence cannot yet establish.